2013
DOI: 10.1007/s00586-013-2918-y
|View full text |Cite
|
Sign up to set email alerts
|

Motion characteristics of the lumbar spinous processes with degenerative disc disease and degenerative spondylolisthesis

Abstract: Objective Recently, interspinous process devices have attracted much attention since they can be implanted between the lumbar spinous processes (LSP) of patients with degenerative disc disease (DDD) and degenerative spondylolisthesis (DLS) using a minimally invasive manner. However, the motion characters of the LSP in the DLS and DDD patients have not been reported. This study is aimed at investigating the kinematics of the lumbar spinous processes in patients with DLS and DDD. Methods Ten patients with DDD at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…The range of inter-vertebral axes or vertebral displacements, measured from no movement (minimum displacement between two successive frames at the neutral or at the end-of-range position) to maximum, was as follows: inter-vertebral axis translation (2.35 cm/L2–L3), inter-vertebral axis rotation (17.29°/L2–L3), vertebral translation (1.34 cm/L2), and vertebral rotation (15.86°/L2) displacements; inter-vertebral axis translation (1.95 cm/L3–L4), inter-vertebral axis rotation (11.42°/L3–L4), vertebral translation (1.23 cm/L3), and vertebral rotation (13.09°/L3); and vertebral translation (0.94 cm/L4) and vertebral rotation (8.49°/L3); the maximum range of movements was observed at the upper axis (L2–L3) and the cranial L2 vertebra for all translation and rotations. The range of excursions, quantified at the upper intervertebral axis and the L2 vertebra, were similar to overall range of motion reported in earlier studies studying physiologic range of the lumbar spine motion [14,20,21].…”
Section: Resultssupporting
confidence: 81%
“…The range of inter-vertebral axes or vertebral displacements, measured from no movement (minimum displacement between two successive frames at the neutral or at the end-of-range position) to maximum, was as follows: inter-vertebral axis translation (2.35 cm/L2–L3), inter-vertebral axis rotation (17.29°/L2–L3), vertebral translation (1.34 cm/L2), and vertebral rotation (15.86°/L2) displacements; inter-vertebral axis translation (1.95 cm/L3–L4), inter-vertebral axis rotation (11.42°/L3–L4), vertebral translation (1.23 cm/L3), and vertebral rotation (13.09°/L3); and vertebral translation (0.94 cm/L4) and vertebral rotation (8.49°/L3); the maximum range of movements was observed at the upper axis (L2–L3) and the cranial L2 vertebra for all translation and rotations. The range of excursions, quantified at the upper intervertebral axis and the L2 vertebra, were similar to overall range of motion reported in earlier studies studying physiologic range of the lumbar spine motion [14,20,21].…”
Section: Resultssupporting
confidence: 81%
“…Besides, significant differences were found in left/right rotation at all three levels. Yao et al reported that, in non-weight-bearing supine, standing, and extension positions, ISP were physically smaller in patients with DDD than healthy subjects [11]. In the current study, similar trends were exhibited in all groups.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, we could determine the positions of specific vertebrae and spinous processes for each pose. In a similar study by Yao et al [11], the accuracy of this technique was within 0.6 mm for translation and 1.3° for rotation.
Fig. 1 a MR image of human lumbar spine of DDD patients.
…”
Section: Methodsmentioning
confidence: 52%
See 1 more Smart Citation
“…Instability in the clinical context designates a condition that not only is thought to be denoted by excessive vertebral movements in response to applied loads, and suggests that these excessive displacements result in pain, progressive deformity and risk of neurologic damage. 8,43,44 Inspection, palpatory assessment and passive testing of vertebral mobility and pain with prone instability testing in the clinic, palpation of step-off and straight leg raise tests form the mainstay of clinical diagnosis of spine instability. The quintessential radiological assessment of instability being the calculation of static, end-range inter-vertebral displacement from radiographs in maximum flexion and extension (first reported in 1944), it is hardy a guess that interpretations of spine stability from static end-points on dynamic stability of spine segments across their ROM, may be misleading.…”
Section: The Next Level Of Complexity: Anatomical Instabilitymentioning
confidence: 99%